Cord blood screening for congenital infectious diseases and haematological change in Sulaimani Provence. - Ameen, Sirwan Muhammed; sadiq, Chinar hameed; rasul, Samira Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2017)
Aims: to determine the seroprevalence of immunoglobulin A (IgA) and immunoglobulin G (IgG) anti-Toxoplasma, anti- Helicobacter pylori antibodies in cord blood serum and to access the usefulness of haematological parameters in diagnosing of toxoplasmosis and H. pylori infection. Toxoplasma gondii specific IgA, IgG and H. pylori specific IgG antibodies were assessed by Chorus enzyme immune assay. 19 out of 70 (27.1%) cord blood serum samples were found positive for anti-Toxoplasma gondii IgG antibody and there was only one (1.4%) positive for IgA. Regarding the detection of specific anti -H. pylori IgG, 30 cord blood samples were tested in which 26 (86.6 %) were found positive and four (13.4%) negative. The positive mean with H. pylori infection was significantly greater than H. pylori-negative mean (88.37 ± 53.69 and 5.8 ± 0.46, respectively, P = 0.005). The comparison of hematological profiles between positive and negative cord blood samples (IgG ≥ 8 and IgG < 4; IgA >1.2 and IgA < 0.8) showed no statistically significant variations in higher and lower value of IgG and IgA titration (P > 0.05). Conclusions: The Results revealed that all the cord blood serum samples were negative for IgA antibodies except one sample (1.4%), indicate that all these newborn infants were rarely infected with congenital toxoplasmosis. Neonates born from H. pylori–infected mother, are provided with a high amount of specific IgG H. Pylori antibodies, which are transferred transplacentally. The complet blood picture (CBC) test shows the non-significant effect of T. gonidii and H. pylori on most of the hematological parameters.
Keywords: Cord blood,Congenital Toxoplasmosis,H pylori,Haematology